A Critical Study of Functions and Contribution of Regulatory Authorities of Food Laws In India: - (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The foremost responsibility of food control is to enforce the foodlaw(s) protecting the consumer against unsafe, impure and fraudulentlypresented food by prohibiting the sale of food not of the nature, substance orquality demanded by the purchaser. Confidence in the safety and integrity ofthe food supply is an important requirement for consumers. Food borne disease outbreaks involving agents such as Escherichia coli,Salmonella and chemical contaminants highlight problems with food safety andincrease public anxiety that modern farming systems, food processing andmarketing do not provide adequate safeguards for public health. Factors whichcontribute to potential hazards in foods include improper agriculturalpractices; poor hygiene at all stages of the food chain; lack of preventivecontrols in food processing and preparation operations; misuse of chemicals;contaminated raw materials, ingredients and water; inadequate or improperstorage, etc.